2007
DOI: 10.1093/jn/137.12.2616
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Access Differentially Modifies 11β-Hydroxysteroid Dehydrogenase-1 and Hexose-6-Phosphate Dehydrogenase Message in Liver and Adipose Tissue in Rats ,

Abstract: 11Beta-hydroxysteroid dehydrogenase-1 (11beta-HSD-1) plays a key role in the regulation of intracellular glucocorticoid concentrations. Increased message and/or activity of adipose 11beta-HSD-1 are characteristics of human and animal models of obesity. Hexose-6-phosphate dehydrogenase (H6PDH) is colocalized with 11beta-HSD-1 and may be a critical factor in determining the oxo-reductase activity of 11beta-HSD-1. This study examined the effects of sucrose solution access on body weight, body composition, and mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…Voluntary sucrose solution intake also restores food intake, weight gain and circulating triglyceride, leptin and insulin levels in ADX rats suggesting that dietary sugar can trigger enhanced peripheral glucocorticoid production and/or affect behavior to compensate for the absence of adrenal activity. More recently, we have shown that rats given free access to 16% sucrose solution in addition to chow and water for 10 weeks have increased 11β-HSD-1 and H6PDH message in mesenteric adipose [45]. These changes in adipose are accompanied by a decrease in 11β-HSD-1 message and increase in H6PDH message in liver in comparison to controls given ad lib access to chow and water.…”
Section: Do Dietary Components Particularly Cho Influence the Hypotmentioning
confidence: 89%
See 1 more Smart Citation
“…Voluntary sucrose solution intake also restores food intake, weight gain and circulating triglyceride, leptin and insulin levels in ADX rats suggesting that dietary sugar can trigger enhanced peripheral glucocorticoid production and/or affect behavior to compensate for the absence of adrenal activity. More recently, we have shown that rats given free access to 16% sucrose solution in addition to chow and water for 10 weeks have increased 11β-HSD-1 and H6PDH message in mesenteric adipose [45]. These changes in adipose are accompanied by a decrease in 11β-HSD-1 message and increase in H6PDH message in liver in comparison to controls given ad lib access to chow and water.…”
Section: Do Dietary Components Particularly Cho Influence the Hypotmentioning
confidence: 89%
“…While there is evidence to suggest that diet and macronutrient composition can influence glucocorticoid metabolism and carbohydrate intake can impact pentose phosphate pathway flux [45], it is not clear how intake is involved in changing the activity or expression levels of these enzymes. Additionally, there is no clear mechanism to explain how 11β-HSD-1 or H6PDH expression and/or activity levels are increased or decreased in a tissue-specific manner in obesity.…”
Section: Hexose-6-phosphate Dehydrogenase and Its Role In Glucocorticmentioning
confidence: 99%
“…Over time however this result washes out and total caloric intake returns to a level that resembles control (70,74).…”
Section: Intakementioning
confidence: 99%
“…Despite the extensive behavioral examinations of the rat"s avidity for sugar solutions, relatively little work has been focused on the impact of sugar intake on the hepatic and central mechanisms controlling intake. We have more recently added to this literature by reporting that fructose consumption can promote increased oxoreductase activity of 11 beta hydroxysteroid dehydrogenase -1, an enzyme that regulates intracellular glucocorticoids in adipose tissue (70,71).…”
Section: Introductionmentioning
confidence: 99%
“…Includes an increased mass of adipose tissue that may lead to hypertension (Klop, 2013) and cardiovascular diseases (London, 2007 andFantuzzi, 2005). Furthermore, obesity has hazardous effects on liver and antioxidant enzyme.…”
Section: Introductionmentioning
confidence: 99%